The art of memory forensics : detecting malware and threats in Windows, Linux, and Mac memory - Ligh, Michael Hale; Case, Andrew (Digital forensics researcher); Levy, Jamie; Walters, Aaron (John Wiley and Sons, 2014)
"The Art of Memory Forensics" is a practical guide to the rapidly emerging investigative technique for digital forensics, incident response, and law enforcement. Memory forensics has become a must-have skill for combating the next era of advanced malware, targeted attacks, security breaches, and online crime. As breaches and attacks become more sophisticated, analyzing volatile memory becomes ever more critical to the investigative process. This book provides a comprehensive guide to performing memory forensics for Windows, Linux, and Mac systems, including x64 architectures. Based on the authors' popular training course, coverage includes memory acquisition, rootkits, tracking user activity, and more, plus case studies that illustrate the real-world application of the techniques presented. Bonus materials include industry-applicable exercises, sample memory dumps, and cutting-edge memory forensics software. Memory forensics is the art of analyzing RAM to solve digital crimes. Conventional incident response often overlooks volatile memory, which contains crucial information that can prove or disprove the system's involvement in a crime, and can even destroy it completely. By implementing memory forensics techniques, analysts are able to preserve memory resident artifacts which often provides a more efficient strategy for investigating modern threats.